Kenya Exports Performance Overview - World Bank (World Bank, Washington, DC, 2017)
Kenya's economy has been running on one engine. Kenya's strong engine is domestic consumption, which accounts for 75 percent of Gross Domestic Product (GDP). Kenya's weak engine remains its exports, which have been declining sharply in relative importance. Kenya's top four main exports do not earn enough to pay for oil imports, not to mention other imports. It will be very difficult for Kenya to achieve high growth over an extended period of time because of its existing economic imbalances. Kenya needs to increase its export competitiveness. It is clear that Kenya's trade performance is below its potential. The objective of this overview is to provide some of that analysis and to contribute to the policy dialogue on the role of exports Kenya's future growth. This paper focuses on five issues: 1) overall trade orientation and export growth; 2) merchandise export trends; 3) merchandise exports by sector; 4) merchandise exports by destination; and 5) diversification. The growth of merchandise exports has been slow and volatile. The average annual growth rate of merchandise exports has been only 10 percent. And while countries such as Vietnam have has a distinct export growth trajectory with steady growth in merchandise exports year after year, Kenya's pattern has been rather volatile with a few good years followed by major falls. Export growth has been driven primarily by existing products in existing markets. Overall there has been little new product/new market discovery.